(untitled) (Vietnam Journal of Community Medicine, 2025)
Fasciola spp. in humans is currently a common disease in Vietnam, especially in the Central Highlands. The disease has symptoms similar to many other digestive and hepatobiliary diseases, so it is easy to misdiagnose and treat late. The gold standard for diagnosing the disease is finding fluke eggs in the stool, but this is rarely observed. In practice, the diagnosis of the disease is mainly based on clinical symptoms, liver damage on imaging and testing to detect antibodies against Fasiola spp. in the serum. This study was conducted to compare the similarity or diagnostic value between commercial ELISA diagnostic test reagents currently circulating in Vietnam. Each reagent set was tested on 34 serum samples of healthy people and 34 serum samples of cases infected with Fasciola spp. determined by clinical symptoms, liver lesions on ultrasound, Western blot test for antibodies against Fasciola spp.. The results showed that the sensitivity of ELISA reagents of Viet Sinh company produced in Vietnam, Cortez produced in the US, DRG produced in Germany, NewLife produced in the US were 91.18%, 91.18%, 100%, 91.18%, respectively; The specificity was 97.06%, 85.29%, 97.06%, 94.18%, and the accuracy was 94.12%, 88.23%, 98.53%, 92.65%, respectively. Compared with the confirmed cases, the Kappa coefficient of the 4 test chemicals was 0.882; 0.765; 0.971; 0.853, respectively. Comparing the agreement between the 4 test chemicals, DRG, Viet Sinh, and New Life had the highest similarity coefficient (Kappa > 0.8). Therefore, the 4 commercial chemicals tested in the study all had good diagnostic value.